Amlodipine-induced angioedema: An unusual complication of a common medication. (April 2018) - Kuruvilla, Merin E.; Sanan, Neha
Hypersensitivity reactions to dihydropyridine calcium channel blockers (CCB) are exceedingly rare, although sporadic reports of isolated angioedema seem to be gradually increasing in frequency. We present a case of angioedema likely triggered by amlodipine.